2005
DOI: 10.1002/mop.20836
|View full text |Cite
|
Sign up to set email alerts
|

Application of the T-chart for solving exponentially tapered lossless nonuniform transmission-line problems

Abstract: seven attenuator sets with the load resistances shown for the FET parameter extraction. The largest four data sets may then be utilized for the final equation solving. Note that the input powerlevel adjustments follow the rules of maximizing N-harmonic levels with higher-order terms in noise-flow levels for N-order coefficient evaluations. SOLUTION ACCURACY EVALUATIONThe extracted coefficients of the FET, shown in Table 2, use the four data sets selected according to the conversion-ratio rules and the addition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
31
0

Year Published

2005
2005
2009
2009

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 4 publications
0
31
0
Order By: Relevance
“…One class of transmission lines (TLs), called conjugately characteristicimpedance transmission lines (CCITLs), has been introduced recently in the literature [1][2][3][4][5][6][7]. By definition, a CCITL possesses conjugate characteristic impedances Z ± 0 of waves propagating in the opposite directions along the transmission line.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One class of transmission lines (TLs), called conjugately characteristicimpedance transmission lines (CCITLs), has been introduced recently in the literature [1][2][3][4][5][6][7]. By definition, a CCITL possesses conjugate characteristic impedances Z ± 0 of waves propagating in the opposite directions along the transmission line.…”
Section: Introductionmentioning
confidence: 99%
“…By definition, a CCITL possesses conjugate characteristic impedances Z ± 0 of waves propagating in the opposite directions along the transmission line. Examples of CCITLs are reciprocal lossless uniform TLs, nonreciprocal lossless uniform TLs [8][9][10], exponentially tapered lossless nonuniform TLs [2,11,12] and periodically loaded lossless TLs operated in passband [13][14][15][16][17][18]. Using the ABCD matrix technique, it can be shown that the equation of the input impedance at each terminal of loaded finite lossless periodic structures is in the same form as that of CCITLs [4].…”
Section: Introductionmentioning
confidence: 99%
“…Conjugately characteristic-impedance transmission lines (CCITLs) have found various applications in microwave technology [1][2][3][4][5][6][7]. Examples of CCITLs are reciprocal lossless uniform transmission lines (TLs), nonreciprocal lossless uniform TLs, exponentially tapered lossless nonuniform TLs [3,8] and periodically loaded lossless TLs operated in passband [10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Examples of CCITLs are reciprocal lossless uniform transmission lines (TLs), nonreciprocal lossless uniform TLs, exponentially tapered lossless nonuniform TLs [3,8] and periodically loaded lossless TLs operated in passband [10][11][12][13][14][15]. In general, CCITLs are lossless and possess different characteristic impedances, which are complex conjugate of each other, for waves propagating in opposite directions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation